(untitled) (Undergraduate Conference on Applied Linguistics, Linguistics, and Literature, 2022)
This study deals with Metaphors Meaning Found in Songs Lyric of Black Holes and Revelations Album by Muse. The aims of this research were to find out the types of metaphorical in the lyrics of Muse song and to find out the most doinant type in the lyrics of Muse songs. The data of this research was taken from video on youtube. This research used Lakoff and Johnson theory to identify the types of metaphor. This study applied qualitative descriptive method. The techniques or collecting data was downloading and watching the videos from youtube, listening it carefully for several times, and printing the lyrics. The data in this research was analyzed by reading the lyrics in several times, identifying the types of metaphor in the lyrics of Muse songs, underlining it in the printed text that related to types of metaphor and finding out the most dominant type of metaphor. It was found there were 26 metaphors, 4 structural metaphors (15.4%), 15 orientational metaphors (57.7%) and 7 ontological metaphors (26.9%) in this research. The most dominant tpe was orientational metaphor, the total was 15 metaphors (57.7%). Thus, teacher can use song lyrics in teaching poetry. On the other hand, students can also improve their understandig in figurative language especially in metaphor by learning through song lyrics.